Kebebasan Individu dalam Tinjauan Filsafat Eksistensialisme Jean Paul Sartre - Muhamad Fauzan; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
In compiling this study, researchers used qualitative methods with an approach to literature study. The result of this study is that humans can become independent as long as their actions benefit mankind. Sartre has two distinct themes in his philosophy of consciousness (existence) and freedom. Freedom became an essential theme in the philosophy of Sartre. Sartre analyzes much about freedom and the way of human existence. According to Sartre, there are two